Sobressemeadura de espécies hibernais com e sem leguminosas em capim aruana na produção de bovinos de corte - Mohr, Alana (2024)
The objective of the study is to determine animal production, pasture, animal behavior and carcass characteristics of beef steers, testing the use of overseeding of winter species with or without legumes in Aruana pasture. The treatments evaluated were: overseeding of oats and ryegrass, with and without vesicular clover in Aruana pasture and extreme cultivation of oats and ryegrass in an area of crop-livestock integration, with and without vesicular clover. The work was carried out between July 10th and October 22nd, 2018 in the beef cattle sector of the Federal Technological University of Paraná, Dois Vizinhos. 24 castrated Angus steers were used, aged 25 ± 3 months and with an average initial live weight of 413.08 ± 4.56 kg. The experimental design was in randomized blocks containing four treatments with three replications (paddocks) in a 2X2 factorial. The animals were distributed among the treatments, two per paddock. Continuous grazing method was used and forage mass, daily accumulation rate and structural composition of the pasture were determined every 21 days. To determine the average daily gain (ADG), animal load (AC) and gain per area (GPV/ha), the animals were weighed after fasting from liquids and solids for 14 hours. Three assessments of the animals' ingestive behavior were carried out over a period of 24 hours each. At the end of the experimental period, the animals were slaughtered to evaluate carcass characteristics. Overseeding and the presence of legumes did not interfere with the nutritional value of the pasture offered to the animals, however the presence of clover increased the leaf:stalk ratio. Animals finished in overseeding had greater average daily gain, better quantitative carcass characteristics, longer rumination time and less displacement when compared to the extreme system. Animals in an overseeded system had less grazing time and more rumination time, with less detachment in search of food.